Edge-enriched and S-doped carbon nanorods to accelerate electrochemical kinetics of sodium/potassium storage. (5th January 2023) - Sun, Bing; Zhang, Qin; Xu, Wenli; Zhao, Rong; Zhang, Chengzhi; Guo, Jianguang; Zhu, Hui; Yuan, Guanming; Lv, Wei; Li, Xuanke; Yang, Nianjun
Abstract: Hard carbon is regarded as a promising anode material for sodium/potassium-ion batteries, which have attracted much attention in grid-scale energy storage. However, it still suffers from the sluggish electrochemical kinetics rooted in the turbostratic structure of carbon, leading to an inferior rate capacity. Herein we utilize a facile strategy to fabricate the edge-enriched and S-doped carbon nanorods (SCNs) with controllable diameter and highly-oriented carbon layer arrangement. The abundant edges lead to the shorter diffusion path of ions, as well as the enlarged layer spacing, both contribute to the rapid kinetics of ionic insertion/desertion. Such a unique highly-oriented structure enables the SCNs anodes to deliver excellent rate capacities and long-lasting cycling life for both sodium and potassium ion storage. The density functional theory (DFT) results demonstrate the enhanced adsorption and reduced ions diffusion energy barrier of Na + ions near the S-doped active sites, which substantiates the promoted electrochemical kinetics of SCNs electrodes. This work inspires more ideas for rational design of advanced electrodes and provides an in-depth insight into the reaction kinetics of carbonaceous anodes. Graphical abstract: Edge-enriched and S-doped carbon nanorods (SCNs) that are constructed by vertically aligned carbon layers are employed as anodes for SIBs and PIBs. They provide abundant active edge-plane sites, a large layer spacing, and short diffusion pathways for Na/K ions, thus feature enhanced capacitive behavior and reaction kinetics. This work will inspire the design of more electrodes for high-rate batteries. Image 1